(untitled) (Scientific journal of the Fergana State University, 2023)
This article aims to study the etymon "joy" in the Uzbek language and the phraseological units in which they are used, as well as to explain their meaning and types, to determine the etymon "joy". In the course of the study, descriptive, classification and historical-comparative methods, as well as synchronic and diachronic aspects, were used. According to the results of this study, the study of the etymology of form and meaning, types and definitions of phraseological units associated with the expression etymon "joy" will be used as an additional source in future studies of the Uzbek language, in the fields of etymology and phraseology of linguistics, and can be used to create names. This article discusses phraseology and etymology, which studies the history of the emergence of words. In the study of the etymology of words, the etymons of "joy" was selected, and the phraseological units in which they were used were researched and explained. As a conclusion of this study, the study of the etymology of words shows not only that there is an influence on the importance of words in current use, but also that it can be reflected in the content of phraseologies.